SISTEM MONITORING DAN PENGENDALIAN SUHU RUANGAN DI LABORATORIUM DENGAN MENGGUNAKAN LABVIEW BERBASIS ARDUINO - Agus Sumarjono (Integrated Lab Journal, 2018)
The change of temperature or working climate could affect one’s working performance, who accidently or purposely be in designated environment. Overheat or over cold could decrease someone’s performance. Hence, a technology on automatic monitoring and temperature or climate controlling should be developed, by employing LabView software with microcontroller Arduino type UNO controlling system, temperature sensor LM-35 and DHT-11. This research, in terms of room temperature monitoring and controlling, will follow several stages: 1. Requirement identification, 2. Analysis of neccesities, Program Design (Software), 4. Tool Engineering (Hardware), 5. Control Programming (Arduino Software), 6. Prototype, 7. Testing. The results of applied methods, could ease the automatic temperature’s monitoring and controlling as required. Therefore, can be concluded that the objective of this research is to increase someone’s effectivity in performing his activities under standard temperature based on the principles of Occupational Safety and Health (OSH). It could be implemented also as learning media especially at the Department of Electrical Engineering.